2021
DOI: 10.56093/ijas.v91i1.110923
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrated farming system on residue recycling, nutrient budgeting and soil health

Abstract: In this study, the effects of integrated farming system on residue recycling and soil quality in rice-based integrated farming systems have been examined. The effective nutrient budget for nitrogen was found higher with rice-fishpoultry- cowpea and the negative values were obtained for rice-chili and rice-baby corn systems. However, the effective budgets for phosphorus and potassium were negative in all these cropping systems. The results indicated that, about ten tonnes of organic matter was recycled, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 13 publications
(8 reference statements)
0
18
0
Order By: Relevance
“…Bieluczyk et al (2020) found that shifting from extensive low-grazing pasture to integrated crop-livestock increased soil organic carbon while introducing eucalyptus rows led to a decrease and subsequent intensification (from integrated croplivestock to integrated crop-livestock-fish) resulted in reduced soil organic carbon and nitrogen stocks indicating the positive effects of integrating the agricultural components for better soil health. However, the degree to which the various processes and nutrient fluxes in the soil are affected is dependent on the type of crops added to the cropping system, nutrient management, and animal components (Paramesh et al, 2021). Integrating livestock and fisheries with crops enhances nutrient use efficiency, nutrient recycling, and soil microbial activity, and reduces external fertilizer dependence, highlighting the positive influence of the IFS farm role in sustainable nutrient management to improve soil health (Sujatha & Bhat, 2015).…”
Section: Needs and Componentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Bieluczyk et al (2020) found that shifting from extensive low-grazing pasture to integrated crop-livestock increased soil organic carbon while introducing eucalyptus rows led to a decrease and subsequent intensification (from integrated croplivestock to integrated crop-livestock-fish) resulted in reduced soil organic carbon and nitrogen stocks indicating the positive effects of integrating the agricultural components for better soil health. However, the degree to which the various processes and nutrient fluxes in the soil are affected is dependent on the type of crops added to the cropping system, nutrient management, and animal components (Paramesh et al, 2021). Integrating livestock and fisheries with crops enhances nutrient use efficiency, nutrient recycling, and soil microbial activity, and reduces external fertilizer dependence, highlighting the positive influence of the IFS farm role in sustainable nutrient management to improve soil health (Sujatha & Bhat, 2015).…”
Section: Needs and Componentsmentioning
confidence: 99%
“…The integration of components establishes an ecological balance and harmonious relationship between agriculture and natural ecosystems, leading to significant contributions to biodiversity conservation. IFS farms integrate polycultures (annual, perennial crops, vegetables, flowers, and spices), livestock or fish with crops, cover cropping, fodder production, and rotational grazing at a single farm, resulting in heterogeneous landscapes that support overall agrobiodiversity (Paramesh et al, 2021). Duru et al (2015) stated that the intensification of ecological interactions between biophysical system components within the farm plays a vital role in conserving the microbial biodiversity in the soil as it promotes fertility, productivity, and resilience to external inputs.…”
Section: Conserving Biodiversitymentioning
confidence: 99%
See 3 more Smart Citations